Algol anomaly or careful observations of its brightness? The values recorded for the magnitude of Algol in the medieval astronomical corpus. (February 2021) - Mozaffari, S. Mohammad; Drake, Jeremy J.
The historical evidence from the past two millennia show two problems concerning the star Algol (β Per): First, a critical variation in its brightness from a magnitude m ~ 2 in (1) Ptolemy's Almagest (2nd century AD) and reported by (2) al-Ṣūfī (10th ct.) through its diminution to m  = 4 in (3) the star catalog prepared by the Persian astronomers in service of the Yuan dynasty of China in the 13th ct. to becoming brighter, m  = 3, as reported by (4) Ibn al-Shāṭir (14th ct.) and (5) Tycho Brahe (16th ct.). In the early modern period, it returned back to m ~ 2, as reported, for example, by Hevelius and Flamsteed (17th ct.), before the discovery of its periodic variability in 1783. Second, al-Ṣūfī reports it as a red star. We present detailed analyses of the sources (3) and (4) for the test of their accuracy and reliability. Our conservative hypothesis concerning the first problem is that the past astronomers observed the star at various phases of its 3-day period of variability. We reject the reddening to have arisen from the extinction due to either the Earth's atmosphere or an interstellar medium. For resolving both problems, we instead speculate on astrophysical explanations for the observations. These are: copious dust produced as a result of arrested coronal mass ejections or pulverized planetary debris that resides close to the central binary before being dispersed; and a much-enhanced accretion rate that lead Algol into a W Ser-like state in which the primary was enveloped in an inflated accretion disk. We draw an analogy between the dimming of Algol and the recent dimming of Betelgeuse in order to highlight the value of historical observations for understanding astrophysical phenomena.